2017
DOI: 10.1007/s12040-017-0802-6
|View full text |Cite
|
Sign up to set email alerts
|

Variable influence on the equatorial troposphere associated with SSW using ERA-Interim

Abstract: Sudden stratospheric warming (SSW) events are identified to investigate their influence on the equatorial tropospheric climate. Composite analysis of warming events from Era-Interim (1979-2013) record a cooling of the tropical lower stratosphere with corresponding changes in the mean meridional stratospheric circulation. A cooling of the upper troposphere induces enhanced convective activity near the equatorial region of the Southern Hemisphere and suppressed convective activity in the off-equatorial Northern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Moreover, some of the recent works show the enhancement of the frequency of SSWs under forcing of GHGs and ODSs (e.g. Huebener et al, 2007;Charlton-Perez et al, 2008;Bell et al, 2009;Schimanke et al, 2013;Ayarzagüena et al, 2013). Thus, the joint effect of the negative trend in solar cycle strength and the positive trend of GHGs may just reduce positive correlation but cannot be its cause.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some of the recent works show the enhancement of the frequency of SSWs under forcing of GHGs and ODSs (e.g. Huebener et al, 2007;Charlton-Perez et al, 2008;Bell et al, 2009;Schimanke et al, 2013;Ayarzagüena et al, 2013). Thus, the joint effect of the negative trend in solar cycle strength and the positive trend of GHGs may just reduce positive correlation but cannot be its cause.…”
Section: Discussionmentioning
confidence: 99%
“…We used the algorithm established by Schimanke et al (2013) which is also used by Bal et al (2017) to calculate the warming dates from Era-Interim. This numerical scheme was developed with a backbone following Charlton and Polvani (2007).…”
Section: Selection and Classification Of Sswmentioning
confidence: 99%
“…The competition between planetary waves and gravity waves to the residual mean circulation associated with different types of sudden warming are studied by Limpasuvan et al (2012) and Albers and Birner (2014). Recently, Bal et al (2017) studied the influence of northern hemisphere warming events on the convective activity in the equatorial troposphere using Era-Interim.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of works are devoted to the role and propagations of gravity waves in times of SSWs (Limpasuvan et al, 2011(Limpasuvan et al, , 2012McLandress et al, 2012;de Wit et al, 2014;Ern et al, 2016). Recently, an effect on the troposphere (Hinssen et al, 2011) and equatorial latitudes has been found (Bal et al, 2017). More about SSWs and related fields can be found in reviews of this subject (e.g.…”
Section: Introductionmentioning
confidence: 99%